Estimating the burden of disease and the economic cost attributable to chikungunya, Andhra Pradesh, India, 2005-2006 - Seyler, T; Hutin, Y; Ramanchandran, V; Ramakrishnan, R; Manickam, P; Murhekar, M (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2010)
To estimate the burden and cost of chikungunya in India, we searched for cases of fever and joint pain in the village of Mallela, Andhra Pradesh, and collected information on the demography, signs, symptoms, healthcare utilization and expenditure associated with the disease. We estimated the burden of the disease using disability-adjusted life years (DALYs). We estimated direct and indirect costs and made projections for the district and state using surveillance data corrected for under-reporting. On average, from December 2005 to April 2006, each of the 242 cases in the village led to a burden of 0.0272 DALYs (95% CI 0.0224-0.0319) and a cost of US$37.50 (95% CI 30.6-44.3). Overall, chikungunya in Mallela led to 6.57 DALYs and a loss of US$9100. Out-of-pocket direct medical costs accounted for 68% of the total. From January to December 2006 the burden for Kadapa district was 160 DALYs (cost: US$290 000). Over the same period the burden for Andhra Pradesh was 6600 DALYs (cost: US$12 400 000). While the burden was moderate, costs were high and mostly out of pocket.